LETERMOVIR PRIMARY CYTOMEGALOVIRUS PROPHYLAXIS IN ALLOGENEIC HEMATOPOIETIC CELL TRANSPLANT RECIPIENTS: COULD INFECTION AND DISEASE NO LONGER BE A SIGNIFICANT PROBLEM? - Fabian Herrera (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Cytomegalovirus (CMV) infection remains the most common clinically significant infection after allogeneic hematopoietic stem cell transplantation (allo-HCT) and is associated with considerable morbidity and mortality.